1989
DOI: 10.1007/bf00332244
|View full text |Cite
|
Sign up to set email alerts
|

Control of formation of active soluble or inactive insoluble baker's yeast α-glucosidase PI in Escherichia coli by induction and growth conditions

Abstract: Using standard growth conditions (LB medium, 37 degrees C, induction with 5 mM IPTG) yeast alpha-glucosidase PI expressed under the control of the regulated tac-hybrid promoter results in the synthesis of insoluble aggregated alpha-glucosidase granules in Escherichia coli. Under these conditions active soluble alpha-glucosidase amounts to less than 1% of the heterologously produced protein. However, the amount of soluble active alpha-glucosidase was dramatically increased when the strong tac-hybrid promoter wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…But some previous studies have shown that pH can affect the solubility rate of the recombinant proteins, this controversy can be due to the differences of the target recombinant proteins. 28,35 Osmotic or heat shocks lead to production of heat shock protein (HSP) and also uptake of osmolytes molecules like glycine betaine (as chemical chaperone) which stabilize native protein and probably assist in correct, active and soluble folding of proteins. 12 We showed an slight amount of soluble recombinant antibody production 3 h after induction in osmotic shock condition (NaCl 0.5 M, glycine betaine 0.1 mM) which can be attributed to the combined effect of osmotic shock and the role of glycine betaine as a chemical chaperone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But some previous studies have shown that pH can affect the solubility rate of the recombinant proteins, this controversy can be due to the differences of the target recombinant proteins. 28,35 Osmotic or heat shocks lead to production of heat shock protein (HSP) and also uptake of osmolytes molecules like glycine betaine (as chemical chaperone) which stabilize native protein and probably assist in correct, active and soluble folding of proteins. 12 We showed an slight amount of soluble recombinant antibody production 3 h after induction in osmotic shock condition (NaCl 0.5 M, glycine betaine 0.1 mM) which can be attributed to the combined effect of osmotic shock and the role of glycine betaine as a chemical chaperone.…”
Section: Discussionmentioning
confidence: 99%
“…The medium pH was adjusted at 5, 6, 7 or 8 and its effects on soluble expression of GST-hD2 were investigated. 28 To examine heat and osmotic shock responses, the study were performed according to the protocol by Oganesyan et al 12 with some minor modification. Harvesting of cells were performed 3 and 15 h after induction.…”
Section: Optimization Parametersmentioning
confidence: 99%
“…Cells were grown as described for tmtrpA, with the exceptions that kanamycin instead of ampicillin was added for maintenance of pET24a-tmtrpB1 and 20°C instead of 37°C was used, which increased the fraction of soluble protein to about 40% for tmTrpB1 and about 10% for tmTrpB2 (33). Harvesting of cells, cell lysis, incubation with benzonase, heat precipitation of host proteins, and anion exchange chromatography were performed as described for tmTrpA, with the exception that the buffer solutions were supplemented with 40 M pyridoxal 5Ј-phosphate (PLP).…”
Section: Methodsmentioning
confidence: 99%
“…tmTrpA could be produced in soluble form at 37°C, but tmtrpB1 and tmtrpB2 had to be expressed at 20°C to suppress in part the formation of insoluble aggregates (33). The resulting thermostable tmTrpA, tmTrpB1, and tmTrpB2 proteins were purified from the soluble fraction of the cell extract, using a heat step to remove thermolabile host proteins followed by ion exchange chromatography.…”
Section: Production and Purification Of Tmtrpa Tmtrpb1 And Tmtrpb2mentioning
confidence: 99%
“…After the mixture was cooled to 25°C, MgCI2 and ATP were added to the final concentrations of 10 mM and 2.0 mM, respectively, and the solution was incubated at 25"C for 3 h. The enzymatic activity of the oc-glucosidase was assayed as described elsewhere with p-nitrophenyl-oc-D-glucopyranoside as the substrate. 20) The effect of E. coli GroES (Takara) was measured by the addition of the protein (final concentration, 2.2 JlM as a 7-subunit oligomer) together with MgCI2 and ATP.…”
Section: Reactivation Of Thermally Inactivated Oc-glucosidase By Purimentioning
confidence: 99%